1976
DOI: 10.1073/pnas.73.2.604
|View full text |Cite
|
Sign up to set email alerts
|

Menkes disease: a biochemical abnormality in cultured human fibroblasts.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(50 citation statements)
references
References 6 publications
2
47
1
Order By: Relevance
“…A similar inheritance is possible in our pa-tients. The female heterozygotes in the Menkes' syndrome do not usually have distinct abnormalities in their serum and fibroblast copper concentrations (1,2). Therefore the normal values found in the mother are not in disagreement with X-linked inheritance.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A similar inheritance is possible in our pa-tients. The female heterozygotes in the Menkes' syndrome do not usually have distinct abnormalities in their serum and fibroblast copper concentrations (1,2). Therefore the normal values found in the mother are not in disagreement with X-linked inheritance.…”
Section: Discussionmentioning
confidence: 82%
“…The human disease is characterized by abnormalities of the hair, bones, and arteries, and by progressive cerebral degeneration with death usually by 3 yr of age. In both diseases intestinal copper absorption is deficient, serum copper and ceruloplasmin concentrations are low, and cultured fibroblasts have markedly elevated amounts of this cation (1)(2)(3). The connective tissue abnormalReceived for publication 6 November 1981. ities are probably due to a reduction in the activity of lysyl oxidase, a copper-dependent enzyme that initiates the cross-linking of collagen and elastin by catalyzing oxidative deamination of the e-amino groups in certain lysine and hydroxylysine residues (4).…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, the abnormal copper metabolism in cultured skin fibroblasts suggests an additional mechanism attributable to the severe clinical symptoms. 1,4,5 Clinical features of Wilson' s disease are chronic liver disease and/or neurological impairment caused by accumulation of copper in various tissues, principally the liver and brain. 1,2 The defect seems to lie in reduced incorporation of copper into the plasma protein ceruloplasmin (CP) and reduced excretion of copper via the bile.…”
Section: Thus the Distribution Patterns Of Atpase7b In Hepatocytes Mamentioning
confidence: 99%
“…Clinical and pathologic studies in such patients reveal a defect in copper transport across the placenta, the gastrointestinal tract, and the blood-brain barrier resulting in a profound deficiency of copper in affected fetuses and newborn infants (3). The recognition that cultured fibroblasts from patients with Menkes disease accumulate intracellular copper and have impaired copper efflux suggested that the defect in this disorder involves an essential pathway of copper transport (4,5).…”
mentioning
confidence: 99%